Adinugraha Thought: Textual and Contextual Approaches in Understanding Islamic Studies to Deal with Life Problems - Muhammad Maskur Musa (Jurnal Studi Ilmu Sosial dan Politik, 2022)
The life of society, along with the development of the times, makes the problems that occur in life also develop. The development of complex problems makes science necessary to adapt to the conditions that occur in society. Purpose: The purpose of this study is to explain Adinugraha's thoughts: textual and contextual approaches to understanding Islamic studies to deal with life's problems. Methodology: The method used in this research is library research with a descriptive qualitative approach. The type of research used is character studies that examine Adinugraha's thoughts. This data collection technique takes sources from Adinugraha's journals and other journals that are relevant to this research. Results: The results of his research explain that Islamic studies are used as a guide in everyday life in society and in dealing with problems. To comprehend Islamic studies, an approach is required, among which are textual and contextual approaches.In essence, the textualist group is more concerned with the outward meaning of the text. while the contextualist group develops reasoning about the context of the text. It should produce a comprehensive interpretation in Islamic studies by using textual and contextual approaches to interpreting revelation. Based on this explanation, textual and contextual approaches can be used to understand Islamic teachings. Therefore, ideally, a comprehensive interpretation must be carried out using a combination of two approaches at once, namely the textual and contextual approaches.